Determinan Ibu Hamil Kurang Energi Kronis (KEK) dan Anemia - Indrasari, Nelly; Octaviana, Amrina; Widhi Sastri, IGA Mirah (Poltekkes Kemenkes Tanjung Karang, 2022)
Pregnant women who experienced anemia in 2013 were 37.1% and increased in 2018 to as many as 48.9%. In Lampung Province, the largest percentage of women of childbearing age who are at risk of Chronic Energy Deficiency are in Tulang Bawang Barat (17.1%), while the highest percentage of the incidence of Chronic Energy Deficiency in pregnant women is in Tulang Bawang Barat (26.3%). The purpose of the study is to determine the determinants of pregnant women with Chronic Energy Deficiency and Anemia at the Karta Raharja & Marga Kencana Public Health Center, Tulang Bawang Barat Regency in 2020. This research is a correlation analytic study that uses a cross-sectional approach. The subject of this study was pregnant women in the Karta Raharja & Marga Kencana Public Health Center, Tulang Bawang Barat Regency in 2020. Each respondent was observed, interviewed, and examined. The data were processed and analyzed using a logistic test. The results showed that pregnant women who experienced Chronic Energy Deficiency were 22% and those who experienced anemia were 26%. The variables most related to the incidence of Chronic Energy Deficiency are parity above 4 children, 106 times the risk of suffering from malnutrition (95%CI=105.502), pregnant women with age <20 or >35 years are 6 times at risk of experiencing malnutrition (95%CI=6.327 ), and pregnant women with malnutrition were 10 times more at risk of experiencing Chronic Energy Deficiency (95% CI=10.224). The variables most related to the incidence of anemia were parity above 4 children 5 times at risk of developing anemia (95%CI=4.995), pregnant women with age <20 or > 35 years 4 times at risk of anemia (95%CI=3.918), and maternal Pregnant women with birth spacing <2 years are 2 times more at risk of developing anemia (95%CI=1.579).